2003
DOI: 10.1021/ol035733d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lactose-Based S-Linked Sialylmimetics of α(2,3)-Sialosides

Abstract: [reaction: see text] A new approach toward the synthesis of lactose-based S-linked sialylmimetics of alpha(2,3)-linked sialosides is described. These compounds, represented by the general structure 3, were prepared from methyl beta-d-lactoside in 11 steps. It was found that the choice of protecting group was crucial to allow the efficient introduction of sulfur at the 3-position of the galactose ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Previous report also suggest that a 4,6‐ O ‐benzylidene protection pattern plays a very important role in the synthesis of the 3‐thio‐β‐ D ‐galactose derivatives, with the key step involving the conversion of the 3‐OTf gulose derivative to the corresponding galactose derivatives 27,28. In addition, recent reports demonstrated that tetrabutylammonium thioacetate is a useful nucleophile in the successful synthesis of 3‐thiogalactose derivatives when esters were used as protecting groups 29,30.…”
Section: Resultsmentioning
confidence: 98%
“…Previous report also suggest that a 4,6‐ O ‐benzylidene protection pattern plays a very important role in the synthesis of the 3‐thio‐β‐ D ‐galactose derivatives, with the key step involving the conversion of the 3‐OTf gulose derivative to the corresponding galactose derivatives 27,28. In addition, recent reports demonstrated that tetrabutylammonium thioacetate is a useful nucleophile in the successful synthesis of 3‐thiogalactose derivatives when esters were used as protecting groups 29,30.…”
Section: Resultsmentioning
confidence: 98%
“…High yielding inversions at C‐3 of gulopyranosides require protection of the 4,6‐diol as a cyclic acetal and are favoured by use of ester, rather than ether protecting groups at O‐2 42. 48 Two synthetic routes to substrates meeting these requirements were identified and are outlined in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of direct one-step transformation of 22 to 24 by regioselective opening of 4′,6′-O-benzylidene acetal under oxidative conditions (dimethyldioxirane) 38 was not explored. There are a few methods [39][40][41] for the preparation of O-benzoylated lactosyl glycosides with a hydroxyl group at C-3′ including a recently proposed 42 approach for O-benzoylation of the axial hydroxy group in vicinal cis-diols. Diol 25, readily available from 20, was converted via intermediate formation of its orthoester into lactosyl acceptor 26 with the hydroxy group at C-3′.…”
Section: Figure 2 Galactosyl Acceptors 9-12mentioning
confidence: 99%